Receptive speech in children from six to nine years of age - Gligorović Milica; Buha Nataša; Dobrota-Davidović Nada (Specijalna Edukacija i Rehabilitacija, 2018)
The research was conducted with the aim to determine the developmental trend of receptive speech in typically developing children from six to nine years of age. The sample consisted of 111 children with typical development, of both genders (49.5% of girls and 50.5% of boys), aged between 6 and 9.11 years (M=95.09, SD=16.82 in months). Participants were distributed into four age groups. Receptive speech was assessed by the Protocol for the Assessment of Receptive Speech that contains tasks for assessing auditory discrimination, rhyming, word recognition and narrative comprehension. An analysis of variance revealed that age was a significant factor of achievement on rhyming tasks (p≤0.000) and narrative comprehension (p≤0.000). There were no significant age differences in auditory discrimination (p=0.372) and word recognition (p=0.634), although some differences between arithmetic means could be seen in favour of older children. Age can explain around 67% of results variability on rhyming tasks and 56% of variability in narrative comprehension. Significant deviation that would indicate the existence of specific language impairment or intellectual disability was not determined in the participants' results.